Impact of Road Traffic on Mysore Slender Loris Loris lydekkerianus lydekkerianus in Keelaveliyur, Tamil Nadu, India - Lavanya, Ravichandran; Gokula, Varadharajan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Roads directly affect the wildlife by mortality through collisions with vehicles. Mysore slender loris Loris lydekkerianus lydekkerianus is distributed in drier regions of southern India. The present paper deals with the impact of road traffic on Mysore slender loris in Keelaveliyur, Tamil Nadu, India. Road kills were recorded from four roads varied in distance from 8 km to 11 km: Keelaveliyur to Thogaimalai, Keelaveliyur to Melapatti, Keelaveliyur to Othakadai, and Keelaveliyur to Pathiripatti. In total, 41 lorises, consisting of 21 adult females, 12 adult males, three subadult females, and five subadult males, were found killed on road by the road traffic from January 2017 to December 2021. Of the four roads differed in traffic volume, more number of roadkills was found on Keelaveliyur to Othakadai road, followed by Keelaveliyur to Pathiripatti, Keelaveliyur to Melapatti, and Keelaveliyur to Thogaimali. Keelaveliyur to Pathiripatty, though with lesser vehicular traffic, was found with more number of roadkills and can be attributed to the availability of more number of trees not only along the roadside but also perpendicular to the road. Besides, abundance of loris was more along this roadside. Extensive removal of trees along the roadside for developmental activities not only reduced the availability of trees but also the population of loris in and around Keelaveliyur in recent years.